The Influence of Education Health Effects on Knowledge About Teenagers About Dismenorea in SMK Assanadiyah - Erike Septa Prautami (Science Midwifery, 2020)
To know the influence of health education effects on knowledge about teenagers about dismenorea assanadiyah in high school. Type used is all research experiments (quasi eksperimen) with pretest-posttest design. Average youth education health knowledge before it was given about reproductive health in high school assanadiyah poor with 6,19. Average youth having given knowledge about reproductive health education health in high school assanadiyah good 7,59. Any impact education health effects on knowledge about teenagers in assanadiyah high school about dismenorea with the p = 0,000.